Soziologie ohne Mensch?: Umrisse einer soziologischen Anthropologie - Alvear Moreno, Rafael (transcript, 2020)
Where does man stand in contemporary sociology? The inclusion through repression in Jürgen Habermas and Niklas Luhmann in the context of a sociological anthropology